Randomised clinical trial: oesophageal radiofrequency energy delivery versus sham for PPI‐refractory heartburn. Issue 4 (13th July 2020) - Zerbib, Frank; Sacher‐Huvelin, Sylvie; Coron, Emmanuel; Coffin, Benoit; Melchior, Chloé; Ponchon, Thierry; Cholet, Franck; Chabrun, Edouard; Vavasseur, Fabienne; Gorbatchef, Caroline; Zalar, Alberto; Mion, François; et al.
Summary: Background: Oesophageal radiofrequency reduces use of proton pump inhibitors (PPIs) in patients with gastro‐oesophageal reflux disease responding to PPIs. Aim: To determine the efficacy of oesophageal radiofrequency in patients with PPI‐refractory heartburn. Methods: A randomised, double‐blind, sham‐controlled multicentre study was designed to assess the efficacy of oesophageal radiofrequency in PPI non‐responding patients with heartburn. Patients had moderate‐to‐severe heartburn defined by at least 3 occurrences a week, and not improved by continuous PPI treatment. The primary endpoint was clinical success at week 24, defined by intake of less than 7 PPI doses over the 2 preceding weeks and adequate symptom control determined by the patient. Results: Sixty two patients were randomised, 29 to the oesophageal radiofrequency group and 33 to the sham group. Intention‐to‐treat analysis showed that 1/29 (3.4%) and 5/33 (15.1%) achieved the primary endpoint in the oesophageal radiofrequency and sham groups, respectively (NS). There was no significant difference between oesophageal radiofrequency and sham regarding the number of days without heartburn, days with PPI consumption in the last 2 weeks, and patients not taking PPIs. No pH‐impedance parameter was associated with clinical response. The occurrence of adverse events was similar in both groups. Conclusion: This sham‐controlled, randomised study did not demonstrate any efficacy of oesophageal radiofrequency for the treatment of PPI‐refractory heartburn regarding symptom relief or consumption of PPIs. ClinicalTrials.gov NCT01682265.